TRANSPORTATION ACTIVITIES ON CONTENT IMPACT LEAD (Pb) IN AMBIENT AIR IN SEMARANG CITY - Sunoko, Hemma Rya; Hadiyarto, Agus; Santoso, Budi (BIOMA, 2011)
The activity of one affects the transport of air pollution, the exhaust emissions of lead (Pb) is a heavy metal that is a toxin that affects the environment and human health and cumulative.Objective of this study aims to assess the levels of lead (Pb) in the air in the city of Semarang in various locations that have high traffic density and control / control levels of lead (Pb) of air at various street locations that have a level of high density of vehicular traffic so as not to endanger.The study was conducted by taking samples at the time of dense traffic of working days and still in the dry season. Samples were taken at 4 (four) dense traffic locations and 1 (one) location that is not dense traffic, then the analytical laboratory, where the method of sampling the field with gravimetry and spectrophotometric analysis.Based on the results of the research content of lead (Pb) highest at the intersection Bangkong Î¼g/Nm3 of 2.41 and lowest 0.86 in Akpol complex Î¼g/Nm3, by looking at the data there is a tendency increasingly dense traffic density of vehicles using gasoline fuel Pb levels in the air also increases. Based research on the highest levels of lead (Pb) in the air ambeint is in the intersection Bangkong at 2, 41 mg / Nm Â³, this suggests by density of vehicle traffic at the site is also the highest and the effort air pollution control specifically heavy metals lead(Pb) in Semarang need con-tinuous or periodic monitoring of the magnitude of Pb levels in the air, and action modes of transportation system improvements in Semarang.Keywords: Lead (Pb), air pollution.